Pengembangan Katalog Interaktif Aksesoris Pernikahan Adat Sumatera Selatan Berbasis Augmented Reality - Meiyi Darlies; RM Chairil Andri; Liza Utama; Dewi Indasari (Sekawan Institut, 2026)
The preservation of local culture faces serious challenges, particularly among younger genera-tions who tend to view traditional clothing merely as ceremonial costumes without understand-ing the cultural values they embody. To address this issue, this study aims to develop a visuali-zation media based on Augmented Reality (AR) in the form of a catalog of South Sumatran wed-ding attire accessories, accompanied by cultural narratives as an educational effort and a means of digitally preserving traditional heritage. The research employs a Design-Based Research (DBR) approach, starting from the collection of cultural data, content development, and AR ap-plication prototyping, to user testing with target participants. Results indicate a 32% increase in cultural understanding, an average usability score of 82.5 (excellent), and positive user responses toward interactivity, 3D visualization, and contextual audio narration. Qualitative analysis re-veals increased interest in local culture and favorable perceptions of AR as an educational me-dium. These findings confirm that the use of a digital catalog and AR is effective as an interactive, informative, and engaging learning tool that supports the preservation of local cultural heritage.